"Cold calling" in psychiatric follow up studies: is it justified?. Issue 4 (20th August 2003) - Tyrer, P; Seivewright, H; Ferguson, B; Johnson, T
Abstract : Background: The ethics of cold calling—visiting subjects at home without prior appointment agreed—in follow up research studies has received little attention although it is perceived to be quite common. We examined the ethical implications of cold calling in a study of subjects with defined neurotic disorders followed up 12 years after initial assessment carried out to determine outcome in terms of symptoms, social functioning, and contact with health services. The patients concerned were asked at original assessment if they would agree to be followed up subsequently and although they agreed no time limit was put on this. Objectives: To decide if cold calling was ethically justifiable and, if so, to set guidelines for researchers. Design: The study was a cohort study of patients with neurotic disorder treated initially for 10 weeks in a randomised controlled trial. Findings: At follow up by a research medical practitioner 18 of the 210 patients had died and of the remaining 192 patients 186 (97%) were seen or had a telephone interview. Four patients refused and two others did not have interviews but agreed to some data being obtained. However, only 104 patients (54%) responded to letters inviting them to make an appointment or to refuse contact and the remainder were followed up by cold calling, with most patients agreeing readily to the research interview. The findings illustrate the dilemma of the need to get the maximum possible data from such studies to achieve scientific validity (and thereby justify the ethics of the study) and the protection of subjects' privacy and autonomy. Conclusions: More attention needs to be paid to consent procedures if cold calling is to be defended on ethical grounds but it is unreasonable to expect this to be obtained at the beginning of a research study in a way that satisfies the requirements for informed consent. A suggested way forward is to obtain written consent for the research at the time that cold calling takes place before beginning the research.